1993
DOI: 10.1111/j.1471-4159.1993.tb03527.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 125I‐Ferrotransferrin Binding Sites in the Mesencephalon of Control Subjects and Patients with Parkinson's Disease

Abstract: Iron is abnormally accumulated in the substantia nigra pars compacta of patients with Parkinson's disease (PD). Because neuronal and glial iron uptake seems to be mediated by the binding of ferrotransferrin to a specific high-affinity receptor on the cell surface, the number of transferrin receptors could be altered in this disease. The regional distribution of specific binding sites for human 125I-diferric transferrin has been studied in the mesencephalon, on cryostat-cut sections from autopsy brains of contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 22 publications
(15 reference statements)
2
34
1
Order By: Relevance
“…In the latter, increased expression of tissue ferritin, the major intracellular sequester of ferric iron, parallels the distribution of the excess iron and largely implicates nonneuronal (glial) cellular compartments (Youdim, 1994). In marked contrast to the ferritin data, the density of transferrin binding sites remains unchanged or varies inversely with augmented iron stores in the substantia nigra and striatum of PD subjects (Mash et al, 1991;Kalaria et al, 1992;Faucheux et al, 1993;Gelman, 1995). These and analogous findings in normal aging and Alzheimer's disease brain specimens (Dwork et al, 1988;Connor et al, 1992;Kalaria et al, 1992;Faucheux et al, 1993; 1993) have led to the important conclusion that, in contradistinction to the situation in most peripheral tissues, transferrin and its receptor play a limited role, if any, in the sequestration of iron by aging and degenerating CNS tissues (Faucheux et al, 1993).…”
Section: Discussioncontrasting
confidence: 66%
“…In the latter, increased expression of tissue ferritin, the major intracellular sequester of ferric iron, parallels the distribution of the excess iron and largely implicates nonneuronal (glial) cellular compartments (Youdim, 1994). In marked contrast to the ferritin data, the density of transferrin binding sites remains unchanged or varies inversely with augmented iron stores in the substantia nigra and striatum of PD subjects (Mash et al, 1991;Kalaria et al, 1992;Faucheux et al, 1993;Gelman, 1995). These and analogous findings in normal aging and Alzheimer's disease brain specimens (Dwork et al, 1988;Connor et al, 1992;Kalaria et al, 1992;Faucheux et al, 1993; 1993) have led to the important conclusion that, in contradistinction to the situation in most peripheral tissues, transferrin and its receptor play a limited role, if any, in the sequestration of iron by aging and degenerating CNS tissues (Faucheux et al, 1993).…”
Section: Discussioncontrasting
confidence: 66%
“…Prior to 59 Fe labeling, bLf was fully desaturated in formiate buffer (0.2 M formic acid-sodium formiate; containing 0.5 M NaH 2 PO 4 and 25 mM EDTA) at pH 3.8 to give apobLf. 59 Fe (18 nmol) (3-25 mCi/mg Fe, Amersham Pharmacia Biotech) was mixed with a solution containing 0.4 mM nitriloacetic acid and 0.05 M NaOH for 5 min at room temperature, and then the pH was adjusted to 8.2 with NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…59 Fe (18 nmol) (3-25 mCi/mg Fe, Amersham Pharmacia Biotech) was mixed with a solution containing 0.4 mM nitriloacetic acid and 0.05 M NaOH for 5 min at room temperature, and then the pH was adjusted to 8.2 with NaOH. ApobLf (37 nmol) dissolved in 0.1 M Tris-bicarbonate buffer (pH 7.6) was added to the iron solution and then incubated for 45 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…However, two regional analyses of radiolabeled ferrotransferrin binding sites in the mesencephalon have shown that their density was extremely low in the SNpc of controls and was either unchanged or decreased in PD patients (13,14), which indicates that the increase in nigral iron content reported in surviving neurons (4,8,11) and in glial cells (7) may occur (i) by metabolic changes with a higher penetration of iron without any increased density of transferrin receptors on the soma of DA cells, (ii) by receptors located on other parts of DA neurons (i.e., terminals), and/or (iii) by other pathways. A localization of transferrin receptors on DA terminals in the striatum has been suggested by studies of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated mice (15) or MPTPtreated monkeys (16) and human brains taken at postmortem (15,16), but this still needs to be confirmed.…”
Section: Introductionmentioning
confidence: 99%